In vitro antibacterial and antifungal activity of salicylanilide pyrazine-2-carboxylates - Krátký, Martin; Vinšová, Jarmila; Buchta, Vladimír (Medicinal chemistry (Shariqah (United Arab Emirates)), 2012)
The development of new antimicrobial agents for the treatment of infectious diseases remains challenging due to the increasing impact of antibiotic resistance. Since salicylanilides and esters of pyrazine-2-carboxylic acid have been described as potential antimicrobials, we have designed and synthesized a series of 2-(phenylcarbamoyl)phenyl pyrazine-2-carboxylates. These were evaluated in vitro for the activity against fungi and Gram-positive and Gram-negative bacteria. All derivatives showed significant antibacterial activity against Gram-positive strains (MIC ≥ 0.98 μmol/L) including methicillin-resistant Staphylococcus aureus. The most active molecule was 5-chloro-2-(3-chlorophenylcarbamoyl)phenyl pyrazine-2-carboxylate. With one exception these esters were at least partly active against fungi tested strains, in particular against mould strains (MIC ≥ 1.95 μmol/L). The most active antifungal agent overall proved to be 2-(4-bromophenylcarbamoyl)-4-chlorophenyl pyrazine-2-carboxylate.
Keywords: antibakteriální látky; Microbial Sensitivity Tests; Molecular Structure; salicylanilidy; mikrobiální testy citlivosti; Pyrazines; antifungální látky; Antifungal Agents; molekulární struktura; Gram-Negative Bacteria; Salicylanilides; Structure-Activity Relationship; houby; vztahy mezi strukturou a aktivitou; pyraziny; gramnegativní bakterie; Anti-Bacterial Agents; Fungi